Recent advances on development of p21-activated kinase 4 inhibitors as anti-tumor agents - Li, Yang; Lu, Qing; Xie, Chenghu; Yu, Yiming; Zhang, Ao (Frontiers in Pharmacology, 2022)
The p21-activated kinase 4 (PAK4) is a member of the PAKs family. It is overexpressed in multiple tumor tissues and pharmacological inhibition of PAK4 attenuates proliferation, migration, and invasion of cancer cells. Recent studies revealed that inhibition of PAK4 sensitizes immunotherapy and has been extensively exploited as a new strategy to treat cancer. In the past few years, a large number of PAK4 inhibitors have been reported. Of note, the allosteric inhibitor KPT-9274 has been tested in phase Ⅰ clinic trials. Herein, we provide an update on recent research progress on the PAK4 mediated signaling pathway and highlight the development of PAK4 inhibitors in recent five years. Meanwhile, challenges, limitations and future developmental directions will be discussed as well.